Quantitative effects of urban spatial characteristics on outdoor thermal comfort based on the LCZ scheme. (1st October 2018) - Liu, Lin; Lin, Yaoyu; Xiao, Ye; Xue, Puning; Shi, Luyang; Chen, Xin; Liu, Jing
Abstract: Based on the local climate zone (LCZ) scheme, nine typical urban areas in Shenzhen, China were chosen to conduct a field survey to quantitatively analyze the outdoor thermal comfort levels under different urban spatial characteristics. Four integrated indicators, F 1, F 2, F 3, and F 4, were defined based on the Fuzzy-AHP method by considering four different considerations for expressing nine different LCZs. Through physical meteorological measurements and simultaneous human responses on local environments, thermal "neutral" value ranges of three thermal comfort indicators ( TCI ) were obtained, varying from 27 °C to 29.5 °C in PET, from 21 °C to 24 °C in OUT-SET*, and from 28 °C to 29.5 °C in UTCI. Quantitative equations between F i and TCI were expressed by applying Linear, Logarithmic and Cubic models to the calculated F i and TCI values in the nine LCZs. Sampling experiments were conducted to generate near-random sampling F i parameters from a four-dimensional distribution. By referring to thermal "neutral" TCI ranges, six optimal F i combinations were determined and results show that the LCZ 1 B appears a preferable LCZ class for optimizing local-scale thermal comfort conditions in the high-temperature environments in subtropical regions of China. Additionally, the optimal F i combinations provide quantitative theoretical guidance in sustainable urban design and planning. Highlights: Nine typical urban areas are chosen based on the LCZ scheme. Four integrated indicators F 1, F 2, F 3, F 4 are defined based on Fuzzy-AHP method. Thermal "neutral" ranges of thermal comfort indicators ( TCI ) are obtained. Quantitative equations between F i and TCI are expressed. Sampling experiments are conducted for determining optimal F i combinations.